Snack Bar Fortification with Catfish, Green Beans, and Pumpkin as a Self-Enterprise Innovation for Pregnant Women in the KEK program under the Stunting Prevention Movement in Tualang Village Serdang Bedagai Regency - Ahmad Fadli; Emma Novirsari; Suryani Eka Mustika; Vivi Asfianti; Denny Satria; Alfi Sapitri; Syukur Berkat Waruwu (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Abstract: The high number of cases of Chronic Energy Deficiency (CED) is linked to several causes, such as low-income levels and unstable employment (poverty), which result in families' inability to meet the nutritional needs of pregnant women. Low education levels affect the thinking and understanding of pregnant women regarding the importance of nutrition during pregnancy, as well as the limited access to quality healthcare services, including antenatal care facilities, which can lead to delays in the early detection and treatment of CED. This condition needs immediate intervention to anticipate the long-term impacts that can result in risks for both the mother and the newborn who do not receive adequate nutrition. To address this issue, it is necessary to implement a Stunting Prevention Movement program, which includes the provision of supplementary feeding (PMT), education on stunting and balanced nutrition, assistance with entrepreneurship training, and business simulations with a relevant theme.